Geologic-climatic history and zoogeographic significance of the urabá region in northwestern colombia (1970)
The existence of a continuous landbridge connecting Central and South America during the uppermost Cretaceous and/or the lowermost Tertiary  cannot be proven on the basis of presently available field evidence. Scattered outcrops of Upper Cretaceous and Paleocene to Lower Eocene shales indicate the continuation of sedimentation in northwestern Colombia during these time intervals. The volcanic "basement complex" consistsmostly of basaltic igneous rocks which intrude Middle Eocene shales and limestones. The pre-Upper Eocene orogeny and the strong pre-Upper Miocene orogeny led to the temporary uplift of the "Cuchillo bridge" which connected the Western Andes of Colombia with the Serranía del Darién of eastern Panamá. Both these orogenies were followed by periods of subsidence when parts of the previously uplifted areas foundered and were covered by the Oligo-Miocene and Upper Miocene-Pliocene seas, respectively. The main uplift of the northern Andes and of the mountains of southern Central America took place during the uppermost Pliocene and lowermost Pleistocene; vertical movements continued throughout the Pleistocene to the present day. The final connection of Central and South America was established during the Upper Pliocene. The exchange of the Middle and South American faunas during the generally warm Tertiary period was mainly influenced by the emergenceand subsidence of low islands and partial land bridges in southern Central America and northwestern Colombia. On the other hand, faunal migrations in these regions during the Quaternary were mainly determined by the following events: (1) The closing of the last water gap separating Central and South America in the Urabá region during the late Pliocene.  (2) The strong uplift of the South and Central American mountains which caused the expansión of dense tropical forests along the foot hills on the windward side and the increased aridity of the lowlands on the leeward side. The mountains themselves formed new zoogeographic barriers which had not existed before, (3) The alternation of cold-wet and warm-dryclimatic phases throughout the Quaternary. These climatic changes influenced the distribution of forest and non-forest vegetation and also determined the changing altitudinal position of the temperature life zones and their continuity or discontinuity along the slopes of the mountain ranges.  The Urabá region was a transit area for the faunas of the more open and drier vegetation during dry climatic periods of the past and is an important meeting place of various Central and South American forest faunas today.